2023
DOI: 10.3390/physchem3010012
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Precision and Thermal and Absorption Properties of Nanostructures in Aqueous Solutions by Transient and Steady-State Thermal-Lens Spectrometry

Abstract: A simultaneous steady-state and transient photothermal-lens modality was used for both the thermal and optical parameters of aqueous dispersed systems (carbon and silica nanoparticles, metal iodides, surfactants, heme proteins, albumin, and their complexes). Heat-transfer parameters (thermal diffusivity and thermal effusivity), the temperature gradient of the refractive index, light absorption, and concentration parameters were assessed. To simultaneously measure thermal and optical parameters, the time scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 171 publications
0
10
0
Order By: Relevance
“…For thermal lens measurements of dispersed media, the spatial distribution of the thermal properties of the medium is important. It has previously been shown that for dispersed systems, such as aqueous dispersions of fullerenes and nanodiamonds [ 31 , 32 ], as well as complex compounds and proteins (hemoglobin) [ 33 ], there is a decrease in the thermal lens signal compared to true solutions with the same solvent and the same light absorption. This is because the absorption of laser radiation leads to rapid local overheating of dispersed particles, but the temperature distribution profile caused by thermooptical phenomena throughout the sample has a smaller amplitude due to slower heat transfer from the heated dispersed particles to the dispersion medium ( Figure 3 a,b).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For thermal lens measurements of dispersed media, the spatial distribution of the thermal properties of the medium is important. It has previously been shown that for dispersed systems, such as aqueous dispersions of fullerenes and nanodiamonds [ 31 , 32 ], as well as complex compounds and proteins (hemoglobin) [ 33 ], there is a decrease in the thermal lens signal compared to true solutions with the same solvent and the same light absorption. This is because the absorption of laser radiation leads to rapid local overheating of dispersed particles, but the temperature distribution profile caused by thermooptical phenomena throughout the sample has a smaller amplitude due to slower heat transfer from the heated dispersed particles to the dispersion medium ( Figure 3 a,b).…”
Section: Discussionmentioning
confidence: 99%
“…This is because the absorption of laser radiation leads to rapid local overheating of dispersed particles, but the temperature distribution profile caused by thermooptical phenomena throughout the sample has a smaller amplitude due to slower heat transfer from the heated dispersed particles to the dispersion medium ( Figure 3 a,b). If we compare two dispersed systems, with an increase in particle size (e.g., the formation of clusters of nanodiamonds [ 32 ] or with the formation of an albumin complex with an iron(II) complex with 1,10-phenanthroline [ 33 ]), the signal decreases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations